The Influence of Financial Literacy and Financial Inclusion on Preventing Fraudulent Investments (Case of IAIN Palopo Students) - Humaidi Humaidi; Ahmad Syawal Senong Pakata; Kiki Musdalifah (Hasanuddin Economics and Business Review, 2023)
This research aims to analyze the partial influence of financial literacy on the prevention of fraudulent investments, the partial influence of financial inclusion on the prevention of fraudulent investments and to simultaneously analyze the influence of financial literacy and financial inclusion on the prevention of fraudulent investments. This research uses quantitative methods with questionnaires as data collection. The sample used was purposive sampling with a sample size of 100 people. The data analysis used is multiple linear regression. The results of this research show that partially financial literacy and financial inclusion have a positive effect on preventing fraudulent investments. Meanwhile, financial literacy and financial inclusion simultaneously influence the prevention of fraudulent investments.